2022
DOI: 10.1111/bph.15834
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine alleviates ferroptosis in cisplatin‐induced acute kidney injury by activating the Nrf2 signalling pathway

Abstract: Background and purpose: Evidence indicates that ferroptosis plays a key role in acute kidney injury induced by cisplatin. The Nrf2/NRF2 pathway regulates oxidative stress, lipid peroxidation and positively regulates cisplatin-induced acute kidney injury, but its effect along with the alkaloid leonurine, found in motherwort, on ferroptosis after such acute kidney injury remains unclear.Experimental Approach: The anti-ferroptotic effects of Nrf2 and leonurine were assessed in a mouse model of cisplatin-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…The frontiers research studies demonstrated that cisplatin-induced nephrotoxicity could be inhibited by preventing mitochondrial fragmentation and subsequent cell injury and death through sirtuin 3-dependent mitochondrial dynamics remodeling underlying honokiol intervention ( Mao et al, 2022 ). Also, the role of the renoprotective effect of leonurine hydrochloride was achieved by inhibition of lipid peroxide-mediated ferroptosis and activation of Nrf2 ( Hu et al, 2022 ). In addition, renalase agonists may be a new tool to enhance the renoprotective effects ( Curry and McCormick, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frontiers research studies demonstrated that cisplatin-induced nephrotoxicity could be inhibited by preventing mitochondrial fragmentation and subsequent cell injury and death through sirtuin 3-dependent mitochondrial dynamics remodeling underlying honokiol intervention ( Mao et al, 2022 ). Also, the role of the renoprotective effect of leonurine hydrochloride was achieved by inhibition of lipid peroxide-mediated ferroptosis and activation of Nrf2 ( Hu et al, 2022 ). In addition, renalase agonists may be a new tool to enhance the renoprotective effects ( Curry and McCormick, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 For example, one of the TCMs, Leonurine hydrochloride, protects the kidney from CI-AKI by Nrf2 activation and inhibiting lipid peroxide. 32 In addition, the protective effect of Nrf2 activation on kidney was also proved in the lipopolysaccharide (LPS)-induced AKI model under Arbutin. 33 Therefore, we conducted molecular docking experiments with Scu and Nrf2.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Of note, the numbers of cells showing the increased FRET/CFP ratios were relatively few, even in the occluded tubules of the cisplatin-treated kidneys of SMART Tg mice. This suggests that another type of cell death, such as apoptosis, ferroptosis, or necrosis, may simultaneously occur in cisplatin-induced kidney injury 39,40 . The mechanisms underlying cisplatin-induced necroptosis are still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%